(untitled) (Bangladesh Medical Journal, 2019)
Acute coronary syndrome (ACS), a life-threatening manifestation of coronary artery disease, ranges from unstable angina (UA) to acute myocardial infarction (AMI). To reduce the morbidity and mortality resulting from acute coronary syndrome, we should have to find out some predictor or prognostic indicator. A prognostic indicator should be available at the time of initial patient’s evaluation, in order to maximize the potential benefits of early risk assessment. This study designed to evaluate plasma BNP as a prognostic tool in patients with acute coronary syndrome. A prognostic cohort study was carried out with 90 (ninety) acute coronary syndrome patients on the basis of their clinical and laboratory criteria with age range of 30 to 90 years in the department of biochemistry, BSMMU, in collaboration with department of cardiology, NICVD, BSMMU and BIRDEM. Plasma BNP concentrations were measured on enrollment and then grouping of the study subjects were done on the basis of their empirical cut off value of plasma BNP concentration. All the patients were free from heart failure, renal disease, thyroid disease and hepatic disorder. Main outcomes were mortality, morbidity and survival after hospital discharge with or without any disability. All the subjects were categorized into two and to see the significance between two groups in relation to age and sex Unpaired –t test and Chi square test were done. Finally, Binary logistic regression was done. Among 90 acute coronary syndromes patients, there were 74(82.2%) male and 16(17.8%) female with mean age of the study population 51.8 years and the age range of 30 t0 90 years. Among enrolled patients, 24 (26.7%) were NSTEMI and 66 (73.3%) were STEMI that includes 29 (32.2%) anterior MI, 21 (23.3%) inferior MI, 16 (17.8%) other varieties of MI. All the study subjects were grouped into two on the basis of empirical cut off value of plasma BNP 640pg/ml on enrollment. Group I with plasma BNP level less than 640pg/ml includes 57 (63.3%) subjects and group II with plasma BNP more than 640pg/ml includes 33 (36.7%) subjects. Among group I (n=57) good recovery, morbidity and mortality found to be in 41(71.9%), 15(26.3%) and 1(1.8%) patients and those in group II (n=33) found in 6(18.2%), 19(57.6%) and 8(24.2%) patients respectively. Keeping the group I in reference category binary logistic regression analysis done, showing odds ratio 11.5 with p- value 0.000. The odds ratio 11.5 indicates that there is 11.5 times higher chance of getting bad outcome in ACS patients having higher plasma BNP concentrations. Bangladesh Med J. 2017 May; 46 (2): 32-37